Preface in memoriam of Raquel Segovia Martín - Language Value (Universitat Jaume I. Department of English Studies, 2021)
This is the fourteenth issue of Language Value, the journal created by the Department of English Studies at Universitat Jaume I (UJI) over 12 years ago. Since its beginning, the journal has grown and progressed, and, at this moment, it is already indexed and recognised internationally. In this evolution, many persons have left their imprint, some of them from the department that devised this journal. One of these persons was Raquel Segovia Martín, who unfortunately left us one year ago. Raquel arrived at Universitat Jaume I from the University of Pittsburgh (USA), where she had obtained her PhD degree in Languages and Film Studies and taught Spanish language and culture courses. Since very young, she had been interested in the Spanish language: she had finished her bachelor's degree in Hispanic Philology at the Universidad Autónoma de Madrid. However, she saw an opportunity to adapt her profile and to participate in the new project of Universitat Jaume I in 1994, once she had decided to come back to Spain. At this university, she could combine her knowledge of Spanish and English in translation courses and add to it her expertise in film and communication studies. She was a good teacher and a good colleague who left us much too soon. This volume is in memorial of Raquel Segovia Martín, and the articles included in it are all related to her profile: translation, cinema and communication.